1963
DOI: 10.1093/genetics/48.8.943
|View full text |Cite
|
Sign up to set email alerts
|

Variegation Initiated by a Dominant Allele in the Tomato

Abstract: HE locus of Woolly is in chromosome 2 of the tomato, Lycopersicon escu-Zentum, in which the basic chromosome number is 12. Three alleles, in addition to the normal non-Woolly allele, WO+, are known. W O and Wov are dominant and lethal when homozygous, and WO"' is partially dominant and viable when homozygous (RICK and BUTLER 1956). Woolly plants have thicker,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The Mutmap analysis based on genomic comparisons of pooled DNA from plants with mutant and wildtype phenotypes [ 51 , 53 , 54 ] revealed that an FtsH-like protein precursor located on chromosome 4 is the most likely candidate. Taking these results into account, we concluded that this FtsH variegation mutant is dissimilar from the previously published tomato mutants with variegated leaves, including studies of a maternally inherited variegated tomato [ 23 ]; the Woolly mutant [ 25 ]; a recessive allele of yv ( yv mut ) [ 29 ], a cytoplasmic or mitochondrial mutation [ 55 ]. More recent studies on chromosomal mutations in the tomato genome are the Ghost phenotype [ 24 , 27 , 28 , 31 ], DLC [ 46 ], and VG [ 33 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The Mutmap analysis based on genomic comparisons of pooled DNA from plants with mutant and wildtype phenotypes [ 51 , 53 , 54 ] revealed that an FtsH-like protein precursor located on chromosome 4 is the most likely candidate. Taking these results into account, we concluded that this FtsH variegation mutant is dissimilar from the previously published tomato mutants with variegated leaves, including studies of a maternally inherited variegated tomato [ 23 ]; the Woolly mutant [ 25 ]; a recessive allele of yv ( yv mut ) [ 29 ], a cytoplasmic or mitochondrial mutation [ 55 ]. More recent studies on chromosomal mutations in the tomato genome are the Ghost phenotype [ 24 , 27 , 28 , 31 ], DLC [ 46 ], and VG [ 33 ].…”
Section: Discussionmentioning
confidence: 79%
“…The first variegation described in tomato displayed pale green – wild-type green leaf variegation phenotype and was inherited as a dominant maternal trait [ 23 ]. A second variegated tomato was characterised by the dominant nuclear gene, located on chromosome 2, which produced variegated leaves with patches of fewer epidermal hairs and abnormal greens [ 25 ]. This so-called Woolly ( Wo ) mutation is dominant, homozygous lethal and chromosomally unstable.…”
Section: Introductionmentioning
confidence: 99%